A World Without Debt - Barry E. Adler (Washington University Law Quarterly, 1994)
In Part I of this essay, I give a brief description of the collective action problem that Baird identifies as the bankruptcy issue for corporate debtors. In Part II, I explain why I believe there is no collective action problem and give what I believe is an essentially simple explanation of a world without debt. In Part III, I respond directly to the criticisms of a world without debt. Finally, in Part IV, I admit the limits inherent in my view of appropriate bankruptcy policy.
Keywords: Bankruptcy reorganization; Bankruptcy law; Corporate finance; United States